Management of Confiscated Assets by the Prosecutor's Office: A Comparative Study between Indonesia and the United States - Adi Tyogunawan; Mohd. Din; Rizanizarli Rizanizarli; Darmawan Darmawan; Jalal Johari (Administrative and Environtmental Law Review, 2026)
The management of confiscated assets is an important aspect of governance in law enforcement and public financial administration. Confiscated assets function not only as consequences of criminal sanctions but also as state assets that must be managed in an orderly and accountable manner consistent with good governance principles. In Indonesia, the Indonesian Attorney General’s Office holds authority to execute final court decisions, including the management of confiscated and forfeited assets. In practice, administrative challenges persist, including limited technical regulations, weak asset governance, and the underutilization of economically valuable assets. This study analyzes the management of confiscated assets by the Indonesian Attorney General’s Office and compares it with the system in the United States using normative legal research with statutory and comparative approaches. The findings show that asset management in Indonesia remains focused on executing court decisions and is not fully integrated with productive state asset governance, while the United States has developed a more comprehensive model through criminal, civil, and administrative forfeiture supported by specialized institutions and stronger accountability. The study highlights the need to strengthen Indonesia’s regulatory framework and institutional capacity to ensure legal certainty and optimize public financial benefits through improved coordination, adequate storage facilities, stronger security standards, trained personnel, and more efficient auction mechanisms for valuable assets.